Luteolin-3′-O-Phosphate Inhibits Lipopolysaccharide-Induced Inflammatory Responses by Regulating NF-κB/MAPK Cascade Signaling in RAW 264.7 Cells - Jung-Hwan Kim; Tae-Jin Park; Jin-Soo Park; Min-Seon Kim; Won-Jae Chi; Seung-Young Kim (Molecules, 2021)
Luteolin (LT), present in most plants, has potent anti-inflammatory properties both in vitro and in vivo. Furthermore, some of its derivatives, such as luteolin-7-O-glucoside, also exhibit anti-inflammatory activity. However, the molecular mechanisms underlying luteolin-3′-O-phosphate (LTP)-mediated immune regulation are not fully understood. In this paper, we compared the anti-inflammatory properties of LT and LTP and analyzed their molecular mechanisms of action; we obtained LTP via the biorenovation of LT. We investigated the anti-inflammatory activities of LT and LTP in macrophage RAW 264.7 cells. We confirmed from previously reported literature that LT inhibits the production of nitric oxide and prostaglandin E2, as well as the expression of inducible NO synthetase and cyclooxygenase-2. In addition, expressions of inflammatory genes and mediators, such as tumor necrosis factor-α, interleukin-6, and interleukin-1β, were suppressed. LTP showed anti-inflammatory activity similar to LT, but better anti-inflammatory activity in all the experiments, while also inhibiting mitogen-activated protein kinase and nuclear factor-kappa B more effectively than LT. At a concentration of 10 μM, LTP showed differences of 2.1 to 44.5% in the activity compared to LT; it also showed higher anti-inflammatory activity. Our findings suggest that LTP has stronger anti-inflammatory activity than LT.